2000
DOI: 10.1046/j.1471-4159.2000.0752563.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Deficits Associated with Dietary Induction of Decreased Brain Docosahexaenoic Acid Concentration

Abstract: Docosahexaenoic acid (DHA), an n-3 fatty acid, is rapidly deposited during the period of rapid brain development. The influence of n-3 fatty acid deficiency on learning performance in adult rats over two generations was investigated. Rats were fed either an n-3 fatty acid-adequate (n-3 Adq) or -deficient (n-3 Def) diet for three generations (F1-F3). Levels of total brain n-3 fatty acids were reduced in the n-3 Def group by 83 and 87% in the F2 and F3 generations, respectively. In the Morris water maze, the n-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
188
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(203 citation statements)
references
References 61 publications
11
188
0
4
Order By: Relevance
“…Deficits in n-3 FAs have been linked to poor spatial working memory (20,21) and olfactory discrimination and learning (22,23) in rodent models, but results of studies with n-3 supplementation in humans have been mixed (24,25). It is possible that attention to the n-6:n-3 ratio would reveal more consistent results in supplementation studies.…”
Section: Introductionmentioning
confidence: 99%
“…Deficits in n-3 FAs have been linked to poor spatial working memory (20,21) and olfactory discrimination and learning (22,23) in rodent models, but results of studies with n-3 supplementation in humans have been mixed (24,25). It is possible that attention to the n-6:n-3 ratio would reveal more consistent results in supplementation studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, work involving rodents suggests that cognitive behavior is related to DHA status (Moriguchi, Greiner, & Salem, 2000) and that treatment with DHA can reduce the decline of such abilities in an AD model (Hashimoto et al, 2002). This study, which showed the beneficial effect of DHA on episodic memory (avoidance learning ability) in AD model rats, also found an associated increase in DHA corticohippocampal levels and a decrease in products associated with neuronal cell death (Hashimoto et al, 2002).…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 51%
“…Rats on an n-3 PUFA deficient diet for three generations showed a reduction in working memory in the MWM as compared to animals reared on an adequate diet for 3 generation. The rats on the deficient diet had longer latencies for finding the hidden platform (Moriguchi et al, 2000). The deficient rats also showed an increase in brain AA and n-6 DPA and decrease in brain DHA (Moriguchi et al, 2000;Moriguchi and Salem, 2003).…”
Section: Learning and Memorymentioning
confidence: 90%